FAKTOR LINGKUNGAN ALAM SEBAGAI UNSUR HAK INDIKASI GEOGRAFIS BUAH SALAK PONDOH - Murjiyanto, Raden; Andani, Devi; Suci, Ivida Dewi Amrih (PSHPM Untag Semarang, 2024)
This research aims to answer the problem of how natural environmental factors influence Pondoh Sleman salak products which have a certain reputation, quality and characteristics, the efforts made to maintain this reputation, quality and characteristics as requirements for Geographical Indication Rights, and how geographical indication rights can provide legal protection for Pondoh Sleman salak products. The Sleman region is on the slopes of Mount Merapi, whose active volcanic ash experiences a rainy and dry season climate. This research was conducted using normative research methods with an approach to applicable laws and regulations and related legal materials. The resulting conclusion is that geographical factors and the natural environment, including climate, influence the reputation, quality and characteristics of Podoh Salak products. Geographical Indication Rights provide the benefit of increasing product value by using the Pondoh Sleman salak identity. Efforts need to be made to maintain and preserve the surrounding natural environment so that the characteristics, quality and reputation of Pondoh Salak products can be maintained. Geographical Indication Rights provide legal protection for Pondoh Sleman Salak products. The results of this research can help the government make decisions and take steps to protect and maintain the environment, provide legal protection, and increase public awareness to preserve and sustain the environment. Thus, granting Geographical Indication Rights can provide maximum benefits.